Gastroprotective effects of Dicranopteris linearis leaf extract against ethanol-induced gastric mucosal injury in rats - Hussaini, J.; Othman, N.A.; Abdulla, M.A.; Majid, N.A.; Faroq, H.M.; Ismail, S. (Academic Journals, 2012)
Dicranopteris linearis is a medicinal plant commonly used traditionaly in the treatment of many aliments. This study was performed to evaluate the gastroprotective effect of ethanolic extracts of D. linearis leaf extract (DLELE) against ethanol-induced gastric mucosal injury in experimental rats. The rats were divided into four groups respectively pre-treated orally with carboxymethyl cellulose (CMC) solution (ulcer control groups), omeprazole 20 mg/kg (reference group), 250 and 500 mg/kg of DLELE (experimental groups) one hour before oral administration of absolute ethanol to generate gastric mucosal damage. After an additional hour, the rats were sacrificed and the ulcer areas of the gastric walls were determined. The ulcer control group exhibited severe mucosal injury, whereas groups pre-treated with DLELE exhibited significant protection of gastric mucosa. These findings were also confirmed by histology of gastric wall. Significant increases in gastric mucus production and decrease in acidity of gastric content were observed in treated groups with DLELE compare to ulcer control group. In conclusion, treatment with DLELE prior to absolute alcohol has significantly protect gastric mucosa as ascertained grossly by significant reduction of ulcer area, increases in gastric mucus production and decrease the acidity of gastric content and histology by comparatively decreases in gastric mucosal injury, reduction or absence of edema and leucocytes infiltration of submucosal layer compared to ulcer control group. DLELE was able to decrease the acidity and increase the mucosal defense in the gastric area, thereby justifying its use as an antiulcerogenic agent.